The effects of age and sex on the incidence of multiple step saccades and corrective saccades - Ma, Wenbo; Zhang, Mingsha (Frontiers in Aging Neuroscience, 2022)
Objective Although multiple step saccade (MSS) is occasionally observed in healthy subjects, it is more pronounced in patients with aging-related neurodegenerative diseases, particularly Parkinson’s disease (PD). Thus, MSS has been treated as a complementary biomarker for diagnosing PD. Despite the aforementioned knowledge, several questions remain unexplored: (1) How does aging affect MSS? (2) Is there a sex difference in MSS? (3) Are there differences in MSS between vertical and horizontal saccades? (4) Are MSS and corrective saccade (CS) the same behavior? (5) How do age and sex affect CS? The objectives of the present study are to address these questions. Method Four hundred eighty healthy participants were recruited to perform a visually guided reactive saccade task. Participants were divided into six groups according to their ages. Each group consisted of forty male and forty female participants. Eye movements were recorded with infrared eye trackers. Results The incidence of MSS increased as a function of age, whereas the incidence of CS first increased with age 20-49 and then decreased with age 50-79. The incidences of both MSS and CS did not show sex differences. The incidence of MSS in vertical saccades was significantly higher than that in horizontal saccades, and their difference increased with increasing age, whereas the incidence of CS showed a reversed pattern. Conclusion Age and saccadic direction affect the occurrences of MSS and CS differently, indicating that MSS and CS are different saccadic behaviors. In addition, measuring saccades could reliably reflect the function of human’s brain which is affected by aging.